Studies on the effect of impact force on the shape of calcium Alginate beads produced from extrusion dripping method - Nur Faraazrin Mohd Nasir (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Determination of bead shape is important for most of encapsulation application. In this study, the shape of alginate produced by the different process parameters was determined. The process parameters involved in this research were concentration of carboxylmethacellulose (CMC) in calcium chloride solution, concentration of alginate solution and needle size. The viscosity, density and surface tension of alginate solution and gelation bath were measured. The results were according to the typical trend. The diameter of beads produced depends on the size of the needle used. The diameter of beads produced from 0.5 mm needle size was the smallest and the diameter of beads produced from 0.9 mm of needle size was the largest. The larger needle size gave higher rate and the drop produced also with larger diameter. For the shape of the bead, a drop was considered as spherical when the spherical factor (SF) was less than 0.05. The beads produced from lower concentration of alginate solution were more deform in shape (SF>0.05) compared to the beads produced from higher concentration of alginate solutions (SF<0.05). Other than, higher concentration of CMC in calcium chloride solution also gives impact to the beads shape (SF>0.05). Bead shape was strongly affected by the viscosity of the gelation bath. Deformed bead (SF>0.05) was obtained when the gelation bath viscosity was greater than 30 cPs.